From Beveridge to Turner: demography, distribution and the future of pensions in the UK - Hills, John (London, 2006)
"This article outlines the recommendations of the UK Pensions Commission, and the data and analysis on which they were based, including projections of demographic change, trends in private pension saving, and evolution of the state pension system. The Commission concluded that without reform, structural problems with UK pensions would lead to increasingly inadequate and inequitable provision in 15-20 years time. It recommended reforms which would lead to a more generous, more universal and less means-tested state system than would otherwise evolve, and the establishment of a low cost National Pension Savings Scheme, into which employees without good employer provision would automatically be enrolled. The proposals, which have now largely been adopted by the UK government, imply eventual increases both in state spending on pensions as a share of national income and in State Pension Age, but accompanied by measures to facilitate later and more flexible retirement."